Maximizing the sum of a generalized Rayleigh quotient and another Rayleigh quotient on the unit sphere via semidefinite programming - Nguyen, Van-Bong; Sheu, Ruey-Lin; Xia, Yong (Journal of global optimization, 2016)
The problem is a type of “sum-of-ratios” fractional programming and is known to be NP-hard. Due to many local maxima, finding the global maximizer is in general difficult. The best attempt so far is a critical point approach based on a necessary optimality condition. The problem therefore has not been completely solved. Our novel idea is to replace the generalized Rayleigh quotient by a parameter μ and generate a family of quadratic subproblems ( P μ ) ′ s subject to two quadratic constraints. Each ( P μ ) , if the problem dimension n ≥ 3 , can be solved in polynomial time by incorporating a version of S-lemma; a tight SDP relaxation; and a matrix rank-one decomposition procedure. Then, the difficulty of the problem is largely reduced to become a one-dimensional maximization problem over an interval of parameters [ μ ̲ , μ ¯ ] . We propose a two-stage scheme incorporating the quadratic fit line search algorithm to find μ ∗ numerically. Computational experiments show that our method solves the problem correctly and efficiently.